Legitimate Interest of Coastal States in Seabed Mining: Indonesia’s Practice - Puspitawati, Dhiana; Susanto, Fransiska Ayulistya; Rusli, Mohd Hazmi Mohd; Fadli, Moh. (Faculty of Law, Hasanuddin University, 2023)
This paper focuses on the utilization of sea mineral resources in areas within national jurisdiction and in the international seabed area (hereafter known as the Area). It discussesÂ Indonesian laws relevant to seabed mining and the need for such laws to take into consideration the maritime zones and activities in the Area, as stipulated by UNCLOS 1982.Â This paper begins with the identification of potential sea minerals both within national jurisdiction and in the Area. Next, it analyzes the international legal framework on seabed mining, including a discussion on the meaning of